From Warlords to Statelords Armed Groups and Power Trajectories in Libya and Yemen - Ardemagni, Eleonora (ISPI Publications, 2022)
In Libya and Yemen armed groups play a central role. Pervading weak and contested institutions, they have gradually brought their webs of survival, profit and governance under the state umbrella: warlords have become the new lords of the state. Armed groups control most of the energy revenues, critical infrastructure, smuggling and illicit trafficking. Their leaders are multifaceted: they are simultaneously military commanders, tribal chiefs, politicians and businessmen. Combining comparative analysis and case studies, this Report sheds light on the "economic face" of the armed groups and their power trajectories. How do armed groups build networks of profit and loyalty in the territories they hold? How does clientelism mark a continuity trend with former authoritarian regimes?